Digital Collaboration in Early Childhood Assessment: A PRISMA-Based Systematic Review of Research Trends and Gaps (2020-2026) - Mia Rachmawaty; Yufiarti Yufiarti; Sofia Hartati (Journal of Childhood Development, 2026)
This study critically examines research trends and gaps in digital collaboration within early childhood assessment through a PRISMA-based systematic review of 27 Scopus-indexed studies published between 2020 and 2026. The findings reveal that existing research is organised around three dominant yet largely disconnected areas: digital assessment tools, parent–educator communication platforms, and child-focused applications. While digital technologies have improved efficiency in documentation, monitoring, and information sharing, their use continues to reflect functional rather than transformative change. Most platforms facilitate one-way communication, positioning parents as recipients of information rather than active contributors to assessment processes. The review identifies several structural gaps, including the fragmentation of digital systems, the persistence of teacher-centred assessment practices, and the limited empirical validation of digital tools. In addition, child-focused applications remain weakly connected to broader assessment and collaboration frameworks. These patterns suggest that current developments are driven more by technological expansion than by pedagogical integration. This study argues for a shift toward integrated digital ecosystems that support co-assessment, shared decision-making, and meaningful parent engagement. Such an approach is essential for advancing collaborative assessment practices and realising the full potential of digital technologies in supporting holistic child development.